Prevalence of and Factors Linked to Occupational Stress in Public and Private Organizations in Kosovo: Array - Tolaj, Sejdë; Havolli, Ymer; Beqiri, Gent (The Journal of Accounting and Management, 2020)
Stress is emerging as an increasing problem in organizations and companies over the recent decades. Despite the awareness on the risks associated with occupational stress, the growing number of literature on stress, so far no empirical research was done to study the prevalence of stress and associated work stressors of employees in Kosovo. Through quantitative research, this study sought to provide scientific contribution by examining the prevalence of stress and by identifying factors that cause stress among public and private sector employees. Findings revealed a relatively high prevalence of occupational stress among employees, where respondents with 1-20 years of work experience reporting being significantly more stressed than those with more than 20 years of work experience. Moreover, results showed that stress adversely affects job performance of employees with 1-20 years of work experience as well as of female employees. Stressors pertaining to demand, control, support, relationships, role and change were identified to be causing occupational stress among employees, all showing positive significant correlation with stress. Furthermore, both public and private sector employees considered similar factors as stressful, even though public sector employees reported experiencing slightly higher levels of stress.